Model of Shariah governance for empowering Islamic non-governmental organisations in humanitarian mission - Nordin, Nadhirah; Embong, Rahimah; Daud, Normadiah; Abdul Aziz, SumayyaH; Salleh, Siti Fatimah; Ismail, Siti Khatijah; Mohd Arifin, Siti Roshaidai (Hamdard National Foundation, 2020)
This study aims to propose a model of shariah governance for Islamic Non-Governmental Organizations. It will define the true concept of shariah governance from a holistic worldview, then to elucidate its theoretical framework for Islamic Non-Governmental Organizations. The issue of defining shariah governance has received a massive amount of attention since the turn of the 20th century. Initially, the governance principles have been practiced by most organizations all around the world at all levels. However, there is a great diversity between the principles of governance applied in most Western-led institutions with the principles of shariah governance. This leads to the discussion on revisiting the concept of governance from a shariah perspective. The study utilizes the grounded theory, which is a qualitative approach that generates theory from observation. In addition, data collection is also supported through a semi-structured interview method and focused group discussions. The data of this study were then analyzed using thematic analysis. The study makes it clear what is a theoretical framework that constructs this model. This model has a flexible theoretical framework which is explained by essential components which are Iman, Islam and Ihsan, and based on the concept of khalifah. This paper emphasizes that shariah compliance is the fundamental element of shariah organization and thus, shariah governance is an ultimate approach to ensure such observance and hence increase the level of public trust in Islamic Non-Governmental Organizations.